Child deprivation and income poverty in Ghana - Raymond Elikplim Kofinti; Samuel Kobina Annim (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This study assesses temporal and spatial distribution of child deprivation and income poverty using the fifth and sixth rounds of the Ghana Living Standards Survey. The first-order dominance methodology was used to examine five dimensions of deprivation of children aged 7 to 17 years, and the outcomes were compared to the incidence of income poverty. The analyses reveal the following: reduction in child deprivation across all five dimensions over time; wide disparities across geographical areas; and differences in regional rankings of deprivation and income poverty. Distinct policies for child deprivation and income poverty are imperative for different locations in Ghana.
Keywords: I00; I30; I32; I38; 330; deprivation; income; poverty; first-order dominance; children; Ghana